2012
DOI: 10.1080/03004430.2011.646726
|View full text |Cite
|
Sign up to set email alerts
|

Having, loving, and being: children's narrated well-being in Finnish day care centres

Abstract: The aim of this study is to answer the following question: what do children tell about their well-being in Finnish day care centres? The theoretical and methodological framework of this study is based on a narrative approach. The research material was collected by participating in the everyday life of three groups of children and listening to their narratives. The research material, consisting of observations and tape-recorded conversations, is reflected in a model of well-being developed by a Finnish sociolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 24 publications
1
28
0
5
Order By: Relevance
“…Recently, Nordic researchers have carried out studies related to the value of democracy with a special interest on the perspective of children's rights and a focus on children's participation and influence, through which children can construct power for self-determination and solidarity (Bae 2009;Broström 2006bBroström , 2012Einarsdottir 2005Einarsdottir , 2010Emilson 2007Emilson , 2008Jensen 2013;Puroila, Estola, and Syrjälä 2012). The findings have shown that children's opportunities for participation and influence seem to be rather limited and depend on a variety of dimensions, such as practitioners' attitudes, communication between children and practitioners, institutional practices and cultural routines of preschools (Emilson 2007).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nordic researchers have carried out studies related to the value of democracy with a special interest on the perspective of children's rights and a focus on children's participation and influence, through which children can construct power for self-determination and solidarity (Bae 2009;Broström 2006bBroström , 2012Einarsdottir 2005Einarsdottir , 2010Emilson 2007Emilson , 2008Jensen 2013;Puroila, Estola, and Syrjälä 2012). The findings have shown that children's opportunities for participation and influence seem to be rather limited and depend on a variety of dimensions, such as practitioners' attitudes, communication between children and practitioners, institutional practices and cultural routines of preschools (Emilson 2007).…”
Section: Previous Researchmentioning
confidence: 99%
“…In the past few years, discussion on children's rights and participation has increased both in Finnish society and in early childhood education research (e.g., Karila 2012;Puroila, Estola, and Syrjälä 2012;Venninen et al 2014). Yet, this Nordic study calls for further research and discussion on democratic values in Finnish early childhood education.…”
Section: Democracy As Being And/or Becomingmentioning
confidence: 99%
“…These include agentive experiences, social support, loving and nurturing relationships, emotional warmth and stimulating activities (see, e.g. Johnson, 2008;Kim-Cohen, Moffit, Caspi, & Taylor, 2004;Luther & Zelazo, 2003;Puroila, Estola, & Syrjälä, 2012). Positive events in children's lives, child-centred interventions, academic success at school as well as empowering hobbies or interests have also been shown to help children overcome and compensate for potential risk-factors to their well-being (Rutter & Rutter, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The descriptions of partnerships given by both parents and practitioners in our study showed that bilingualism was considered to be the natural state of affairs and that the language choices between practitioners and parents were open to negotiation. Furthermore, the idea of 'the best for the child in the form of loving care' (Puroila, Estola, and Syrjälä 2012) was generally considered to be more important than any strict observance of official language policies. Such attitudes allowed language mixing practices between all stakeholders and gave some linguistic freedom even to the children.…”
Section: Discussionmentioning
confidence: 99%